Quantum Key-Policy Attribute-based Encryption - Gabriela Mogos (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Attribute-Based Encryption is a relatively new concept in the field of cryptography, and it allows only the authorized entities to decrypt a message. This type of encryption is the mechanism by which the users may encrypt and decrypt data based on user attributes. This paper proposes the first quantum alternative of the scheme Key-Policy Attribute-Based Encryption, where the information, the encryption/decryption key, and the attributes are made of qutrits.